Kavējumi un skolēna pašizjūta skolas vidē. - Zaula, Anna (Latvijas Universitāte, 2011)
Maģistra darba tēma ir Kavējumi un 13 – 15 gadus vecu pusaudžu pašizjūta skolas vidē. Maģistra darbs ir izstrādāts, pamatojoties uz teorētiskajām atziņām par izglītības vidi un to veidojošajiem elementiem, par pašizjūtas jēdzienu un tās izpausmēm, mūsdienu pusaudžu raksturīgākajām iezīmēm, kā arī kavējumus veidojošajiem faktoriem. Darba autore veica pētījumu Rīgas X vidusskolā par kavējumu ietekmi uz skolēnu pašizjūtu skolas vidē. Maģistra darba noslēgumā ir izveidotas rekomendācijas izglītības vides uzlabošanai, skolēna pašizjūtas uzlabošanai, kā arī kavējumu mazināšanas iespējām. Darba rakstīšanā izmantota pedagoģiskā, sociālpedagoģiskā, psiholoģiskā literatūra. Tāpat ir apskatīti personālvadības un pozitīvās domāšanas aprakstošā literatūra. Atslēgas vārdi: Izglītības vide, pašizjūta, pubertāte, kavējumi.

The topic of the Master’s thesis is Non-attendance and the Well-being of Students in the School Environment (13 – 15 Years old). The Master’s Thesis has been worked out basing on theories about the education environment and its formative elements, the concept of the sense well-being and its manifestations, the most characteristic features of present day teenagers, as well as the factors causing non-attendance. The author of the Paper carried out a research in Riga Secondary School X about the influence of non-attendance on the well-being of the students in the school environment. Recommendations for improving the education environment, improving the well-being of the students as well as options for reducing non-attendance have been developed in the conclusion of the Master’s Thesis. Pedagogical, social-pedagogical and psychological literature has been used in the process of writing the thesis. In addition, literature on human resources management and positive thinking has been discussed. Key words: Education environment, well-being, puberty, non-attendance.
Student's absence and wellness in school environment.
Keywords: Pedagoģija